Water for elephants - Lawrence, Francis; Waltz, Christoph, 1956-; Schneider, Paul, 1976-; Witherspoon, Reese, 1976-; Pattinson, Robert, 1986-; Holbrook, Hal.; LaGravenese, Richard; Netter, Gil.; Gruen, Sara.; Fox 2000 Pictures; 3 Arts Entertainment (Firm); Flashpoint Entertainment; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2011)
Against all odds, a veterinary student and a beautiful circus performer meet and fall in love through their shared compassion for a special elephant. But their secret romance incurs the wrath of her dangerously volatile husband. Bonus features included.
Widescreen.
Based on the novel by Sara Gruen.
Special features: Robert Pattinson spotlight ; feature performer Reese Witherspoon ; the traveling show page to screen ; audio commentary.
Music, James Newton Howard ; editor, Alan Edward Bell ; director of photography, Rodrigo Prieto.
Reese Witherspoon, Robert Pattinson, Christoph Waltz, Hal Holbrook, Paul Schneider.
MPAA rating: PG-13; for moments of intense violence and sexual content.
Keywords: Circus -- Drama; Depressions -- 1929 -- Drama; Circus performers -- Drama; Elephants -- Drama; Man-woman relationships -- Drama; Feature films; Romance films; Video recordings for the hearing impaired